Minimum Wage Hikes and Technology Adoption: Evidence from U.S. Establishments - Dai, Xin; Qiu, Yue (Journal of Financial and Quantitative Analysis, 2024)
Abstract This article studies the effects of state minimum wage increase on information technology (IT) adoption at the establishment level in the United States. Our results show that treatment establishments on average allocate between $10,328 and $66,808 more per year to their IT budgets during the first 3 years after experiencing significant state minimum wage increases. Additional evidence shows that state minimum wage increases on average lead to an economically small decrease in employment. The estimated employment effect is larger for establishments that have more incentives to automate labor. Our results suggest that establishments adopt technology to countervail increased labor costs.